Measuring the Power of Undervalued Currency to Stimulate Exports - Edelberg, Victor (Review of Economic Studies, 1938)
Journal Article Measuring the Power of Undervalued Currency to Stimulate Exports: Part II Get access Victor Edelberg Victor Edelberg London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 3, June 1938, Pages 195–217, https://doi.org/10.2307/2967447 Published: 01 June 1938